Implementasi Model CCR Data Envelopment Analysis (DEA) Pada Pengukuran Efisiensi Keuangan Daerah - Israwan, LM Fajar; Surarso, Bayu; Frikhin, Farikhin (Universitas Diponegoro, 2016)
Regional budget control system is implemented through an audit and evaluation to ensure that its implementation is in accordance with the plan that it can be efficiently and effectively used. Regional budget efficiency measurement then aims to measure the efficienty of budget use of each Regional Work Unit (SKPD) and to optimalize its use. The efficiency of Regional Work Unit is measured using CCR Data Envelopment Analysis (DEA) model with one input variable and eight output variables, in which this CCR DEA applies Linear Programming approach and evaluates relative efficiency of Decision Making Units (DMUs). The sample was in a total of sixteen DMUs. The result revealed that seven DMUs were efficient, in which their reference set was then used to optimalize the input and output variables of other inefficient DMUs. This result was validated through paired sample t-test, proving to meet the hypothesis of Ho -2,042 â‰¤ tcount â‰¤ 2,042 showing that CCR DEA can be used as a method to measure regional budget efficiency with accurate results.